2019
DOI: 10.4269/ajtmh.18-0740
|View full text |Cite
|
Sign up to set email alerts
|

The Unknown Nature of the Antigen in the Direct Agglutination Test for Visceral Leishmaniasis Hampers Development of Serodiagnostic Tests

Abstract: Abstract.Current diagnostic tests for visceral leishmaniasis (VL) are either not adapted for use in resource-poor settings or are insufficiently accurate in Eastern Africa. Only the direct agglutination test (DAT), based on whole Leishmania promastigotes, is highly reliable in all endemic regions, but its implementation is hampered by the need for a cold chain, minimal laboratory conditions, and long incubation times. Integrating the DAT antigen(s) in an immunochromatographic rapid diagnostic test (RDT) would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…DATs have been used for the diagnosis of VL for more than 30 years and are still widely implemented in South America, Iran and to a lesser extent in Europe (de Korte et al, 1990;Nigro et al, 1996;Mikaeili et al, 2007;Farajnia et al, 2008;Farahmand and Nahrevanian, 2016;Bangert et al, 2018;Sarkari et al, 2018;Kühne and Büscher, 2019). The principle of this assay is to test whether agglutination occurs when serial dilutions of patient serum are mixed with stained killed Leishmania sp.…”
Section: Direct Agglutination Testmentioning
confidence: 99%
See 1 more Smart Citation
“…DATs have been used for the diagnosis of VL for more than 30 years and are still widely implemented in South America, Iran and to a lesser extent in Europe (de Korte et al, 1990;Nigro et al, 1996;Mikaeili et al, 2007;Farajnia et al, 2008;Farahmand and Nahrevanian, 2016;Bangert et al, 2018;Sarkari et al, 2018;Kühne and Büscher, 2019). The principle of this assay is to test whether agglutination occurs when serial dilutions of patient serum are mixed with stained killed Leishmania sp.…”
Section: Direct Agglutination Testmentioning
confidence: 99%
“…The last step is the reading of the end-titer. The end-titer depends on the used protocol, and varies from ≥1/100 for DAT-LPC, 1/1,600 for the DAT from KIT-Biomedical Research, to 1/3,200 (Pedras et al, 2008;Adams et al, 2012;Oliveira et al, 2013;Bangert et al, 2018;Kühne and Büscher, 2019). However, these variations do not seem to influence the test sensitivity and specificity for the clinical diagnosis of VL (Chappuis et al, 2006).…”
Section: Direct Agglutination Testmentioning
confidence: 99%
“…Previously, we hypothesized that the PG repeat epitope of LPG is cleaved off during formaldehyde treatment of the L. donovani promastigotes, thus abolishing this shielding effect (Supplemental Figure 6A). 9 Here, we show a reaction of the monoclonal antibody CA7AE with the DAT Ag, both in the DAT and in the ELISA. This demonstrates that the PG epitope is still present on the DAT Ag, suggesting that the LPG coat on the promastigote cells is rendered porous to antibodies by a reshuffling process (Supplemental Figure 6B).…”
Section: Discussionmentioning
confidence: 76%
“…We recently conducted a literature review on the existing evidence on the nature of the DAT Ag. 9 We found that most of the evidence reported was inconclusive, as most studies were focused on improving the sensitivity and specificity of the antigen rather than determining the identity of the reacting antigen(s)/epitopes. However, based on the observations of these studies, we formulated hypotheses on the nature of the DAT Ag.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation